Stock Return and Factors Influencing Study on Consumer Goods Industry Sector Companies Listed on the Indonesia Stock Exchange in 2020-2023 - Kepramareni, Putu; Putra, Gde Bagus Brahma; Sandiawati, Dwi (Philippine Social Science Journal, 2025)
Focusing on the consumer goods sub-sector of the Indonesia Stock Exchange (2020–2023), this study analyzes financial ratios influencing stock returns to guide sustainable investment decisions. Through non-participant observation and analysis of financial reports from the BEI website, results indicate that Current Ratio (CR), Total Asset Turnover (TATO), Return on Asset (ROA), and Earnings Per Share (EPS) positively affect stock returns, whereas Debt to Equity Ratio (DER) has a negative impact. While these findings offer valuable insights for investors and corporate strategy, future research should extend the observation period to five years and incorporate direct company data to better assess long-term financial conditions.